2006
DOI: 10.1111/j.1365-2249.2006.03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for extrathymic T cell maturation after thymectomy in infancy

Abstract: SummaryOur previous study showed that children who had been partially or completely thymectomized during heart surgery as infants had lower proportions and numbers of total lymphocytes and reduced proportions of T cells (CD3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
(52 reference statements)
4
42
1
Order By: Relevance
“…Previous short-term surveys showed that thymectomized children have reduced CD4 + T cell and TCR excision circle numbers compared with age-matched controls (6)(7)(8)(9)(10). More recently, reduction of naive CD4 + T cell numbers and production in thymectomized patients was shown to correlate with chronological age and time since thymectomy (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous short-term surveys showed that thymectomized children have reduced CD4 + T cell and TCR excision circle numbers compared with age-matched controls (6)(7)(8)(9)(10). More recently, reduction of naive CD4 + T cell numbers and production in thymectomized patients was shown to correlate with chronological age and time since thymectomy (11).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of PBMC samples from YATECs, taken an average of 2 decades after thymectomy, revealed clear alterations in the CD4 + T cell compartment (as expected from previous studies on CHD patients; ref. [6][7][8][9][10][11] as well as in the CD8 + T cell compartment. We found decreased CD4 + and CD8 + T cell counts in YATECs compared with age-matched controls, and even compared with middle-aged adult controls (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…Thymectomy at an early age has been shown to result in reduced CD4 ϩ and CD8 ϩ T-cell numbers, largely due to reduced naive T-cell counts, in the first years after thymectomy. These changes in the T-cell pool at an early age occur without obvious clinical consequences, 14,19,20 although diminished responses to tick-borne encephalitis have been reported. 18 The long-term effects of thymectomy during early childhood on the composition of the T-cell compartment are less unequivocal.…”
Section: Introductionmentioning
confidence: 99%
“…31 Because patients with ADA-SCID show alterations in thymic function and architecture, 32 the increase in gd T cells observed in the GT group could be related to the slow recovery of the thymic activity, implying a disadvantage in the ab TCR rearrangement. Moreover, the expression of CD8aa, a marker associated with extrathymic differentiation, 33,34 was not different across the considered study groups, indicating that after GT, like BMT, the immune reconstitution process is mainly thymus derived.…”
Section: Discussionmentioning
confidence: 87%